Learning Approaches in Biology Learning - Fajar Adinugraha; Adisti Ratnapuri; Andriyan Ino Ponto; Novalina Novalina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
Biology is a subject that learn topics about morphology, anatomy, and physiology, biodiversity, ecosystem, and the environment. Therefore, an appropriate learning approach is needed for students so that the topics will be received by students well. Learning is not only about a transfer of knowledge but also skills and attitudes. This article describes about learning approaches that can be applied to students in Biology. The research was a literature study method from various literature. There are three kinds of learning approaches that appropriate in Biology. They are Scientific Approach, Environmental Exploration Approach, and Local Wisdom and Cultural Approach. The characteristic of the scientific approach was scientific thinking. The characteristics of the Environmental Exploration Approach was an exploration in the environment, such as natural, social, and technology. The characteristic of the local wisdom and cultural approach was ethnobiology and ethnopedagogy studies in learning through science processes based on the level of knowledge, skills and attitudes of students. These three approaches were expected to be an alternative in learning Biology because they contain the principles of scientific processes and student centered learning in them to accommodate 21st-century education.